Assessment Of The Polio 4 Immunization Program: Study At The Puskesmas Rowosari, Pemalang Rural Area - Sofa Fuadiya; Yulis Indriyani; Teguh Irawan; Nadzifa Ziada Amalia; Putri Helmania; Malika Sabina Meiarisanti; Muh. Zuhad Mahya Raul (PT. Anagata Sembagi Education, 2024)
Immunization is still the mainstay of the strategy to reduce the number of infectious diseases in toddlers. In 2023 Rowosari Puskesmas, Pemalang only reached 82.61% of polio 4 immunization achievements which had not reached the 100% target. To assess the evaluation of polio 4 immunization program at Rowosari Puskesmas, Pemalang. This study used a qualitative research type with a descriptive approach. To gather information, in-depth interviews were conducted with five informants, namely the immunization program manager (main informant), two village midwives (supporting informants), and two mothers of children under five (triangulation informants) through direct observation to the research location. Wiyorowetan Village has the lowest immunization achievement, the level of knowledge of mothers of toddlers is still lacking on the importance of immunization, lack of family support in immunization activities, small number of children in immunization implementation, low effectiveness of polio vaccine usage index (IPV) utilization, and lack of support from health workers to remind follow-up immunization schedule. Meanwhile, Bumirejo Village has the highest immunization achievement. This research study found barriers in the knowledge level of mothers of children under five, family support, number of children, utilization of index vaccine use (IPV), and health worker support.